Funkcja rozdzielcza prawa pracy - Kociucki, Leszek (Wydział Prawa i Administracji UAM, 1988)
Distributive function of the labour law is based on the principle of formal justice (the principle of equal measure). The article points out to the features of the labour law which determine the way of carrying out that function: uniformity and differentiation. The article characterizes basic formuli of distribution of goods contained in the Constitution and in the Code and particular formuli contained in acts of lower rank, such as collective bargaining agreements, factory pay agreements, etc. The author points out to some problems connected with the fact that basic formuli of distribution of goods are actually carried out by the acts of the so-called collective labour law. The article presents the classification of formuli of distribution of goods. In concluding remarkis the evaluation of an agreement between particular and basic formuli has been undertaken, with attention paid to some inconsistencies and loosening of ties between some basic and particular formula.
Distributive function of labour law